Improved approach to the estimation of efficiency of energy-saving measures and technologies at TPP - Maliarenko O.Ye.; Gorsky V.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The current state of combined heat and power generation systems in Ukraine by means of cogeneration district heating (CHP) is considered and analyzed. The structure of consumption of different types of fuel by public and industrial thermal power plants is given. The existing methodical approaches to determining the energy-intensity of energy carriers and their types (at the final stage of production and through ver the technological chain) are analyzed. We improved the methodical approach to determination of the through technological energy-intensity of energy carriers, produced in the process of their co-production at thermal power plant with the separcation of energy costs for certain technologies: unloading and preparation of fuel, its submission to burners, burning in a boiler plant, and implementation of nature-conservative measures for environmental protection. We developed and tested a model of the calculation of end-to-end technological energy intensity of energy production at TPPs, which burns coal by two variants of technologies (widespread and newest energy-efficient ones) and for TPPs on natural gas, which use secondary energy resources of excess pressure formed at the reduction of natural gas pressure at a gas-distributing point for the power plant network with the representation of calculated data for each technological process and equipment and summarized final results for each departament and plant in general. In all variants, the electric power of turbine is taken to be identical. This detailing of energy consumption makes it possible to visually represent, analyze and compare variants for upgrading power equipment over all departaments of thermal power plant.